THE RIGHTS OF VICTIMS OF VIOLENCE BY NON-STATE ACTORS IN IRAQ POST-2003 - AL-ANAIBI, FARIS,KAREEM,MOHAMMAD (2018)
Violence and victimisation in Iraq is a long story and, in recent times, specifically in the aftermath of the 2003 controversial occupation of the country by the United States and its allies, and the atrocities committed by so-called ISIS, the situation has escalated to a horrific extent. Ethno-sectarian violence, bombings, armed conflict and enforced disappearances have demonstrated the complete absence of any effective reaction by the state, and this has undermined efforts at consolidation by the Iraqi state and its legal system following the downfall of the previous oppressive regime in 2003. Hundreds of thousands of Iraqi citizens have become victims of violence by non-state actors, largely due to the failure of the 2003-transition process and the flawed constitution and divisive ethno-sectarian system. This fuelled political conflict, widespread corruption, insurgency, terrorism, and extremism, paralysing the Iraqi state and its criminal justice system. This thesis claims that the Iraqi state has failed to provide redress for non-state violence. It further argues, based on international human rights’ instruments, that the state owes positive duties to citizens to protect them from such violence. The thesis will be argue that one method – but not in isolation - of gradually addressing the failings of the Iraqi state would be for Iraqi citizens themselves to take ‘substantive steps’ to ‘establish a healthy civil society reflecting social contract principles.’ Such steps can and should be taken with the support of governmental bodies and other authorities, as part of a genuine and inclusive transitional justice programme in which accountability, truth recovery, reparations, legislative and institutional reform, and reconciliation will be vital, if any future stability and peaceful coexistence is to be established, especially after the ISIS conflict. Despite being a very lengthy task, at present the security situation is gradually improving following the defeat of ISIS. The foregoing steps are arguably also essential for the consolidation of the state and its institutions over the rule of law, in which respect for and protection of the human rights of citizens is the primary objective. This will be imperative in restoring citizens’ trust, confidence, and hope that the Iraqi state and its criminal justice system will gradually honour their positive obligations